Effects of xanthan-locust bean gum mixtures on the physicochemical properties and oxidative stability of whey protein stabilised oil-in-water emulsions - Puli, Goutham; Khouryieh, Hanna; Williams, Kevin; Aramouni, Fadi M. (My University, 2015)
The effects of xanthan gum (XG)-locust bean gum (LBG) mixtures (0.05, 0.1, 0.15, 0.2 and 0.5 wt%) on the physicochemical properties of whey protein isolate (WPI) stabilized oil-in-water (O/W) emulsions containing 20% v/v menhaden oil was investigated. The apparent viscosity of the emulsions containing XG/LBG mixtures was significantly higher (p < 0.05) than the emulsions containing either XG or LBG alone at higher concentrations of XG/LBG mixtures. Locust bean gum showed the greatest phase separation, followed by XG. Microstructure images showed depletion flocculation at lower biopolymer concentrations, and thus let led to an increase in creaming in stability and apparent viscosity of the emulsions. Addition of 0.15, 0.2 and 0.5 wt% XG/LBG mixtures greatly decreased the creaming of the emulsions. The rate of lipid oxidation for 8-week storage was significantly lower (p <0.05) in emulsions containing XG/LBG mixtures than in emulsions containing either of the biopolymer alone.
Keywords: Menhaden oil; Xanthan gum; Locust bean gum; Emulsion; Oxidative stability